The Quality Development of Besuki Na-Oogst Tobacco in Jember Regency - Wardhono, Adhitya; Arifandi, Josi Ali; Indrawati, Yulia (JEJAK: Jurnal Ekonomi dan Kebijakan, 2019)
The purpose of this study was to examine the strategies for improving the quality standardization of Besuki Na-Oogst tobacco cultivation. Data sources were obtained from the results of in-depth interviews with Besuki Na-Oogst tobacco-related stakeholders. The analytical method used was the Analytical Hierarchy Process (AHP). The results of the study showed that the success of Besuki Na-Oogst tobacco cultivation governance as a quality and export-oriented product was not only determined by good cultivation techniques but also needed to be supported by institutional patterns from upstream to downstream, starting from on-farm to off-farm. Trade and marketing are being the main priorities in the development of tobacco quality. Some of the top rankings in alternative strategies are the role of formal institutions in marketing followed by management of quality standards, determination of selling prices and market expansion occupying the priorities of all alternatives in the development of tobacco quality. These results are in line with the important role of quality in export commodities in particular in which quality will affect competitive advantage and ultimately improve the welfare of farmers and other tobacco farming actors.